Traumatic Fact in Adhikari’s “Yojana” - Pokharel, Badri Prasad (Tribhuvan University Journal, 2016)
Abroad study and employment has become compulsive to all Nepali who from the time of school aspire to go abroad so that they would get rid of the transitional turmoil of the country and if possible would settle there. People from middle class go abroad – mostly golf countries to earn money to run the domestic needs. Here, they become vulnerable to fall victims and their dependents would be doomed to lead a painful life. The sole source of the country is remittance such people send from there. However, the government is reluctant to make any plan to stop them from going there and endow them with plenty of opportunities so that they would not have to loiter along the hot sand rather toil in their own cozy soil. Dinesh Adhikari’s “Yojana” (Planning) delineates the situation. This situation has been analyzed from trauma theory.